2015
DOI: 10.1097/mpa.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis E–Associated Acute Pancreatitis

Abstract: Acute pancreatitis associated with hepatitis E is not uncommon and usually has good prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…[11] While none of the hepatitis virus-infected AP patients in the NIS database had HEV, at least 14 case studies of HEV infection associated with AP have been reported in the literature, mainly describing young adults in areas endemic for the virus. [22] A review study identified 55 cases of HEV-associated AP, among which about one-fifth were severe and overall mortality was 3.2%. [23] Kamar et al [24] reported that HEV, despite its association with AP, was also associated with extrahepatic disorders, including hematologic disorders and autoimmune myocarditis and thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…[11] While none of the hepatitis virus-infected AP patients in the NIS database had HEV, at least 14 case studies of HEV infection associated with AP have been reported in the literature, mainly describing young adults in areas endemic for the virus. [22] A review study identified 55 cases of HEV-associated AP, among which about one-fifth were severe and overall mortality was 3.2%. [23] Kamar et al [24] reported that HEV, despite its association with AP, was also associated with extrahepatic disorders, including hematologic disorders and autoimmune myocarditis and thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, several cases of HEV-induced acute pancreatitis have been reported [87][88][89][90][91]. A single-center study from India found that 2.1% (16/790) of patients with acute pancreatitis had serological evidence of a recent HEV infection with no other discernible cause of pancreatitis [92]. The authors suggested that this was due to edema developing in the ambulla of Vater, which then obstructs pancreatic fluid flow.…”
Section: Renal Manifestationsmentioning
confidence: 99%
“…These include neurological disorders such as Guillain-Barré syndrome, neuralgic amyotrophy, and meningoencephalitis [31]; kidney disorders such as cryoglobulinemic glomerulonephritis [32], cryoglobulinemic membranoproliferative glomerulonephritis [33], and exacerbation of IgA nephropathy [34]; and hematological disorders including thrombotic thrombocytopenic purpura [35][36][37] and aplastic anemia [38]. Other extrahepatic manifestations attributed to HEV infection comprise pancreatitis [39][40][41], myocarditis [42,43], and thyroiditis [44,45].…”
Section: Introductionmentioning
confidence: 99%